Immunity to rhythm: Visual or auditory stimuli during intense aerobic exertion do not modulate the mood of young adults - Araujo, Flavio de Souza; Almeida, Camila Maria Menezes; Souza, Mariana Ferreira de; Sales, Marcelo Magalhães; Moraes, José Fernando Vila Nova de (Physical Education and Sports: Studies and Research, 2026)
Background: High-intensity aerobic exercise can promote higher energy expenditure when compared to low and moderate-intensity exercise. However, vigorous exercise can negatively influence mood responses related to adherence. Auditory and audiovisual resources have been used to improve psychological variables during and after exercise. Objectives: To analyze the influence of listening to music and watching video clips on mood responses of young adults after a high-intensity aerobic exercise session. Methods: This is a Cross-Sectional Randomized Controlled Study in which fourteen male participants (23.4 ± 3.1 years; 26.2 ± 3.4 kg/m²) randomly performed exercise sessions on a cyclergometer, at an intensity of 10% above anaerobic threshold, in three situations: control (C), listening to music (M), and watching video clips (VC). At the end of each session, participants underwent 30 min of passive recovery. Mood responses were measured using Brunel’s Mood Scale (BRUMS) before exercise, immediately after exercise, and after recovery. Friedman’s and Wilcoxon’s tests were used, with a significance level of 5%. Results: No statistical differences were found between conditions (C, C, and VC) for the dimensions confusion, fatigue, anger, tension, and vigor (p>0.05). A statistically significant difference was found for depression before exercise, with M higher than C and VC (p<0.05); however, no differences were observed after exercise or recovery. Conclusions: Listening to music and/or watching video clips does not influence mood responses in young adults after high-intensity aerobic exercise on a cyclergometer.